2018
DOI: 10.1071/sh17137
|View full text |Cite
|
Sign up to set email alerts
|

HIV susceptibility among clients of female sex workers in Indonesia: a qualitative inquiry

Abstract: The study results indicate the need to reformulate and improve HIV and AIDS-related services, including increasing the level of availability of HIV service points and the dissemination of knowledge and information about HIV and AIDS and condom use and making them accessible to both FSWs and their clients in Belu and Malaka districts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…A low level of education attainment, which seemed to lead to poor health literacy, including the lack of knowledge about HIV/AIDS and preventive functions of condoms, was also a structural factor that played a role in the spread of HIV among the participants, which is consistent with previous findings of studies with different population groups [ 30 , 31 , 32 , 33 ]. It is plausible to consider health literacy among waria and transgender populations in general as an important factor to address because it affects their ability to access, understand and use health information and health system successfully to manage their own health [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…A low level of education attainment, which seemed to lead to poor health literacy, including the lack of knowledge about HIV/AIDS and preventive functions of condoms, was also a structural factor that played a role in the spread of HIV among the participants, which is consistent with previous findings of studies with different population groups [ 30 , 31 , 32 , 33 ]. It is plausible to consider health literacy among waria and transgender populations in general as an important factor to address because it affects their ability to access, understand and use health information and health system successfully to manage their own health [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although the five dimensions offered by Healthcare access framework (approachability, acceptability, availability, affordability, and appropriateness) [36] seemed to be met by the provision of HIV/AIDS related services for waria in Yogyakarta, it should be noted that these services were only available in a few community health centres and hospitals in the study setting, reflecting unequal distribution of health resources required for HIV/AIDS health service delivery for waria populations as well as other population groups within communities in Yogyakarta and the other parts of Indonesia. Inequity in health service availability has been noted as one of the major barriers to the access to health services by waria and other population groups in Indonesia [4, 9, 4042]. It is also worth noting the current study’s participants’ characteristics that match the five corresponding abilities of the Healthcare access framework (ability to perceive, ability to seek, ability to reach, ability to pay (through possession of health insurances) and ability to engage) (36), resulting into what appeared to be seamless interactions between them and service providers.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant finding as an indication of acceptance MSM by the Yogyakarta community and health sector. As stigma and discrimination are significant barriers to accessing health services ( Mwanri et al, 2018 ), tolerance and a nonjudgmental approach toward MSM, which seem to be the case in this study, could be an important factor ( Tribun Jogja, 2016 , February 25; Wardhana, 2016 , November 28) to enhance positive health and well-being outcomes of MSM in the Yogyakarta city.…”
Section: Discussionmentioning
confidence: 74%
“…However, supportive of previous studies ( Adih & Alexander, 1999 ; Albarracin et al., 2001 ; Bandawe & Foster, 1996 ; Ross, 1992 ), the current study informs that attitudes such as individual beliefs about the positive outcomes or attributes of accessing health services had positive influence on participants’ intention to attend and access HIV/AIDS program. Mwanri et al (2018) claim that limited knowledge or limited information about the existence of the available services and their benefits can hinder access to HIV/AIDS services. The current study observed a similar finding with one of the reasons stated as that many MSM in the province were not reached and may thus not access the HIV/AIDS program.…”
Section: Discussionmentioning
confidence: 99%